ASSESSMENT OF KEY FACTORS CONTRIBUTING TO COST OVERRUN IN SMALL-SCALE CONSTRUCTION PROJECTS IN WEST SUMATRA PROVINCE THROUGH THE PLS-SEM METHOD - Zeni Awalia Putri; Wahyudi P. Utama; Eva Rita (SIGMA TEKNIKA, 2026)
Cost overruns remain one of the most persistent challenges in construction project management, particularly in small-scale projects where limited resources often increase financial risks. This study aims to identify and analyze the factors contributing to cost overruns in small-scale construction projects within the Province of West Sumatra, Indonesia. A quantitative approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires distributed to 100 respondents consisting of project owners, consultants, and contractors. The results indicate that all investigated factors significantly influence cost overruns, with contractor site management identified as the most dominant factor. Poor field management, inadequate supervision, and inefficient scheduling were found to contribute substantially to increased project costs. In addition, weaknesses in financial management, low labor productivity, material price fluctuations, and frequent design changes were identified as critical contributors. The study also emphasizes the importance of effective communication, timely decision-making, and comprehensive project management in minimizing cost escalation. The developed PLS-SEM model demonstrated strong predictive relevance (Q² = 1) and a high Goodness of Fit (GoF = 0.851), indicating its robustness in explaining the factors influencing cost overruns in small-scale construction projects.